Postural alignment and physical exercise extracurricular, preliminary findings - Franco Jimenez, Alejandra Maria [UNESP]; Barrios Puerta, Claudia Marcela; Rojas Jaimes, Diego Alejandro [UNESP]; Aguirre Loaiza, Hector Haney (Univ Manizalez, Fac Medicina, 2016)
Objective: to evaluate the effect of an exercise program on postural alignment students from 8 to 11 years. Materials end methods: a total of eleven students of both sexes randomized, experimental group (GE, n = 6) with mean age 10.0 +/- 1.22 years; and control group (CG, n = 5) 9.50 +/- 0.54 years. The program was implemented in 36 sessions (duration: 45 minutes each session. Frequency: 3 days per week). Postural alignment was evaluated by photogrammetry and analyzed in the Kinovea 0.8.7 program. Results: the data showed an effectiveness of exercise program significantly reducing the misalignment regions chin and breastbone lowin the previous view, vertex and cervical 7 in the rear view. The GC did not show improvements. Conclusion: the exercise program lasting 12 weeks and linear periodization reduces existing postural misalignment and promotes body alignment in school from 8 to 12 years. The implications for clinical and educational level suggests it is recommended prescribing specific physical exercises for the correction of postural misalignments in this age group. Also, to encourage scientific level future work in this line and control of other environmental factors
Keywords: school health; posture; exercise; postural alignment; photogrammetry